2005
DOI: 10.1086/491743
|View full text |Cite
|
Sign up to set email alerts
|

Protection against LethalAspergillus fumigatusInfection in Mice by Allogeneic Myeloid Progenitors Is Not Major Histocompatibility Complex Restricted

Abstract: Invasive fungal infections are a leading cause of morbidity and mortality after myelotoxic chemotherapy or radiation exposure. The resulting depletion of myeloid precursors under these conditions appears to be the factor that limits approaches to accelerate immune reconstitution. In a murine model of myeloablation after radiation exposure, we demonstrated that highly purified common myeloid and granulocyte-monocyte progenitors (CMPs/GMPs) accelerated myeloid recovery and, thus, enhanced innate immunity as meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 14 publications
0
25
0
Order By: Relevance
“…In murine studies of MHCmismatched allogeneic HCT it was shown that in vivo CMP produce a single wave of mature myelo-erythroid cells, that this reconstitution is faster than the reconstitution from HSC, that they do not persist long term and that their progeny is functional in vivo as demonstrated by radioprotection and protection against fungal infections. 15,16 In our present study, we document a functional correlation for the human counterparts of these progenitors by correlating the progenitor contents in clinical graft products with time to engraftment. A potential future clinical application of these findings could be the add-back of purified CMP and MEP from G-PBMC to accelerate the engraftment of patients undergoing CB transplantation where prolonged transfusion-dependent thrombocytopenia is still a major problem.…”
Section: Cd34mentioning
confidence: 64%
See 1 more Smart Citation
“…In murine studies of MHCmismatched allogeneic HCT it was shown that in vivo CMP produce a single wave of mature myelo-erythroid cells, that this reconstitution is faster than the reconstitution from HSC, that they do not persist long term and that their progeny is functional in vivo as demonstrated by radioprotection and protection against fungal infections. 15,16 In our present study, we document a functional correlation for the human counterparts of these progenitors by correlating the progenitor contents in clinical graft products with time to engraftment. A potential future clinical application of these findings could be the add-back of purified CMP and MEP from G-PBMC to accelerate the engraftment of patients undergoing CB transplantation where prolonged transfusion-dependent thrombocytopenia is still a major problem.…”
Section: Cd34mentioning
confidence: 64%
“…8 The hallmarks of these committed progenitors are a limited life span of several weeks, a loss of self-renewal potential and the in vivo production of a single wave of mature hematopoietic cells of the respective cellular lineage. Functionally, myelo-erythroid progenitors were shown to confer radioprotection, 15 as well as protection against invasive fungal infections, 16 lymphoid progenitors were shown to protect against viral infections post transplant in mice. 17 Furthermore, murine studies of hematopoietic aging showed a shift in the mouse BM progenitor compartment because of an increased percentage of myeloid progenitors in aged mice as compared with young mice.…”
Section: Increasing Numbers Of Cd34mentioning
confidence: 99%
“…MPs are progeny of HSCs with the potential to give rise to myeloid, erythroid, and granulocytic cells of the blood system. Infusion of these cells in neutropenic hosts has been shown to provide transient resistance to fungal and bacterial pathogens in a nonmajor histocompatibility complexdependent fashion (86,87). A recent study in an animal model indicates that MPs can be added to allogeneic HSC grafts without affecting tolerance induction (88).…”
Section: Tolerance Inductionmentioning
confidence: 99%
“…Myeloid progenitor cells have been shown to be of special interest in this respect because they can be cryopreserved, used independent of major histocompatibility complex matching, and provide rapid and mostly transient engraftment that provides protection against bacterial and fungal pathogens (86,87,92).…”
Section: Reviewmentioning
confidence: 99%
“…However, progenitor cells are capable of partially restoring functional hematopoiesis for a limited period of time [26][27][28] . A combination of CMP/ GMP isolated from the bone marrow has been shown to protect myeloablated mice from otherwise lethal doses of pathogenic fungus or bacteria in syngeneic and allogeneic mouse models 26,29,30 . Furthermore, purified populations of CMP or MEP but not GMP protect lethally irradiated congenic mice from death in a dose-dependent manner 28 .…”
Section: Use Of Progenitors In Radiation Casualtiesmentioning
confidence: 99%